CONCEPTUAL STUDY OF THE EFFECT OF MADHU IN NEONATAL PAIN MANAGEMENT (AYUSHDHARA, 2016)
New born under go various minor procedures like venipuncture for various purposes. The ability of neonates to perceive pain and to react is fully or nearly fully developed in the neonatal period as most of the anatomical pathways and neurotransmitter necessary for pain perception are developed. The prevention of pain is important not only because it is an ethical expectation but also because repeated painful exposures can have deleterious consequences. Procedural pain causes physiological changes in the body of a neonate, where an inflammatory response to the damaged tissues is initiated, while a stress response induces hormonal and metabolic changes affecting stability of the homeostasis.An Ayurvedic approach should be considered in the field of Kaumarbhritya for Vedanasthapan in newborn as an alternative or better medicine than common available modern drugs.According to Ayurveda, pain is initiated by Vata and activities of Vata are mainly perceived through Rakta Dhatu as illustrated in Charak Samhita. Thus any kind of Aghat will sensitize the pain perception via Rakta Dhatu.Madhu a Shonitsthapan drug with Sandhaniya property is expected to reduce the Raktadushti and eventually reducing the pain perception.This review is carried out with an aim to understand the pain perception mechanism in Ayurvedic principle and to formulate Ayurvedic management protocol. The presentation of neonatal pain management is critically reviewed from various database and classical texts.